Estimating Myocardial Infarction Size With a Simple Electrocardiographic Marker Score. Issue 3 (4th February 2020) - Lee, Daniel C.; Albert, Christine M.; Narula, Dhiraj; Kadish, Alan H.; Panicker, Gopi Krishna; Wu, Edwin; Schaechter, Andi; Pester, Julie; Chatterjee, Neal A.; Cook, Nancy R.; Goldberger, Jeffrey J.
Abstract : Background: Myocardial infarction (MI) size is a key predictor of prognosis in post‐MI patients. Cardiovascular magnetic resonance (CMR) is the gold standard test for MI quantification, but the ECG is less expensive and more widely available. We sought to quantify the relationship between ECG markers and cardiovascular magnetic resonance infarct size. Methods and Results: Patients with prior MI enrolled in the DETERMINE (Defibrillators to Reduce Risk by Magnetic Resonance Imaging Evaluation) and PRE‐DETERMINE Trial and Registry were included. ECG leads were analyzed for markers of MI: Q waves, fragmented QRS, and T wave inversion. DETERMINE Score=number of leads with [Q waves×2]+[fragmented QRS]+[T wave inversion]. Left ventricular ejection fraction (LVEF) and infarct size as a percentage of left ventricular mass (MI%) were quantified by cardiovascular magnetic resonance. The Modified Selvester Score estimates MI size from 37 ECG criteria. In 551 patients (aged 62.1±10.9 years, 79% men, and LVEF=40.3±11.0%), MI% increased as the number of ECG markers increased ( P <0.001). By univariable linear regression, the DETERMINE Score (range 0–26) estimated MI% ( R 2 =0.18, P <0.001) with an accuracy approaching that of LVEF ( R 2 =0.22, P <0.001) and higher than the Modified Selvester Score ( R 2 =0.09, P <0.001). By multivariable linear regression, addition of the DETERMINE Score improved estimation of MI% over LVEF alone ( P <0.001) and over Modified Selvester Score alone ( P <0.001). Conclusions: In patients with prior MI, a simple ECG score estimates infarct size and improves infarct size estimation over LVEF alone. Because infarct size is a powerful prognostic indicator, the DETERMINE Score holds promise as a simple and inexpensive risk assessment tool.